Economic Sociology Discovering Economic Geography (translated by E. Golovlyanitsina) - Patrik Aspers; Sebastian Kohl; Dominic Power (Journal of Economic Sociology, 2010)
The paper reviews the ﬁ eld of economic geography and searches for  opportunities of potential collaboration with the economic sociology. Firstly, a short history of economic geography as a research ﬁ eld is presented. Then some classic and modern geographical concepts embedded in economic geography are reviewed. Finally, the authors discuss how economic geography and sociology can be brought together and indicate perspectives for mutual collaboration